A value co-creation model for wine tourism. (2015) - Festa, Giuseppe; Vrontis, Demetris; Thrassou, Alkis; Ciasullo, Maria V.
In spite their significant wine heritage, even major wine-producing countries still lack a corresponding systemic vision. This research highlights the possible contribution of a relational perspective on the management of wine tourism systems, underlining the necessity for the development of chains, networks, constellations, flows, and service(s). Specifically, the research develops a scientific framework supportive of the relational perspective on wine tourism to aid all major stakeholders in understanding, designing, and developing a wine tourism structured system based on service-dominant logic. The research is based on a speculative analysis of relational governance in wine tourism, and develops a theoretical framework of the relational context of wine tourism. The research is further supported by a field investigation focusing on the Campania Region (Italy); and a case study that enhances the understanding of the subject and indicates the potential implications of the framework, as well as its practical and theoretical applications.